A Guanidyl‐Based Bivalent Peptidomimetic Inhibits K‐Ras Prenylation and Association with c‐Raf. Issue 59 (9th September 2019) - Tsubamoto, Mai; Le, Toan Khanh; Li, Minghua; Watanabe, Taku; Matsumi, Chiemi; Parvatkar, Prakash; Fujii, Hiroshi; Kato, Nobuo; Sun, Jiazhi; Ohkanda, Junko
Abstract: Unusual lipid modification of K‐Ras makes Ras‐directed cancer therapy a challenging task. Aiming to disrupt electrostatic‐driven protein–protein interactions (PPIs) of K‐Ras with FTase and GGTase I, a series of bivalent dual inhibitors that recognize the active pocket and the common acidic surface of FTase and GGTase I were designed. The structure‐activity‐relationship study resulted in 8 b, in which a biphenyl‐based peptidomimetic FTI‐277 was attached to a guanidyl‐containing gallate moiety through an alkyl linker. Cell‐based evaluation demonstrated that 8 b exhibited substantial inhibition of K‐Ras processing without apparent interference with Rap‐1A processing. Fluorescent imaging showed that 8 b disrupts localization of K‐Ras to the plasma membrane and impairs interaction with c‐Raf, whereas only FTI‐277 was found to be inactive. These results suggest that targeting the PPI interface of K‐Ras may provide an alternative method of inhibiting K‐Ras. Abstract : Cell‐permeable bivalent dual inhibitors for FTase and GGTase I were designed aiming to disrupt protein–protein interactions with K‐Ras. Cell‐based evaluation demonstrated that the compound inhibits K‐Ras processing without apparent interference with Rap‐1A processing. The compound was also shown to disrupt localization of K‐Ras to the plasma membrane and impairs interaction with c‐Raf, a downstream effector.